Endoscopic management versus radical nephroureterectomy for localized upper tract urothelial carcinoma in a high endemic region - Chen, Yung-Tai; Yu, Chih-Chin; Yeh, Hsin-Chih; Lee, Hsiang-Ying; Jiang, Yuan-Hong; Lee, Yu-Khun; Kuei, Chia-Hao; Wu, Chia-Chang; Huang, Chao-Yuan; Lin, Wei-Yu; Yang, Cheng Kuang; Tsai, Yao Chou (Scientific reports, 2021)
Our aim was to analyze the clinical and survival differences among patients who underwent the two main treatment modalities, endoscopic ablation and radical nephroureterectomy. This study examined all patients who had undergone endoscopic management and RNU between Jul. 1988 and Mar. 2019 from the Taiwan UTUC registry. The inclusion criteria were low stage UTUC in RNU and all cases in endoscopic managed UTUC with a curative intent. The demographic and clinical characteristics were included for analysis. In total, 84 cases in the endoscopic group and 272 cases in the RNU group were enrolled for final analysis. The median follow-up period were 33.5 and 42.0 months in endoscopic and RNU group, respectively ( p = 0.082). Comparison of Kaplan–Meier estimated survival curves between groups, the endoscopic group was associated with similar overall survival (OS), cancer specific survival (CSS), and intravesical recurrence free survival (IVRS) but demonstrated inferior disease free survival (DFS) ( p = 0.188 for OS, p = 0.493 for CSS and p < 0.001 for DFS). Endoscopic management of UTUC was as safe as RNU in UTUC endemic region.